Proteomic Analysis of the Hepatopancreas of Chinese Mitten Crabs (Eriocheir sinensis) Fed With a Linoleic Acid or α-Linolenic Acid Diet - Wei, Banghong; Yang, Zhigang; Cheng, Yongxu; Zhou, Junyu; Yang, Hang; Zhang, Long; Yang, Xiaozhen (Frontiers in Physiology, 2018)
As representatives of n-6 and n-3 fatty acids, many studies have analyzed the use of soybean oil and linseed oil rich in linoleic acid (18:2n-6, LA) and α-linolenic acid (18:3n-3, LNA) as better substitutes for fish oil. In aquatic animals, different dietary ratios of LA and LNA could have significant effects on growth, lipid metabolism, immune response, and reproduction. To assess the nutritive value of these two fatty acids in Chinese mitten crab (Eriocheir sinensis), we performed transcriptome analysis and label-free quantification proteomic analysis of the hepatopancreas from mitten crabs fed with LA or LNA diet. Parallel reaction monitoring was used to confirm the reliability of the proteomic analysis. A total of 186 proteins were differentially expressed with fold change ≥1.5 or ≤0.666. Among the 186 proteins, 116 were upregulated and 70 were downregulated in the LA than LNA. Most of these proteins participate in cellular process and metabolism process and have molecular functions such as binding and catalytic activity; the cellular component of these proteins are cell, cell part, membrane, and membrane part. A total of 18 proteins were identified to be related to lipid, carbohydrate, and protein metabolism, and they mainly participate in digestive enzyme activities, fatty acid transport, and glycolysis. Our results provide new insights for further investigation into the replacement of fish oil from mitten crabs with vegetable oils and enable us to better understand the different roles and nutrition value of LA and LNA in mitten crabs.